Analisis Pengaruh Financial Stability, Financial Target, dan External Pressure Terhadap Fraudulent Financial Statements - Susanto, David Agus; N, Natalia; Steven, Michael; Jauhari, Chicirya Agnes (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
All companies have almost the same goal, namely to seek or get maximum profit. This causes some parties to make mistakes in the company's financial statements, either intentionally or unintentionally. Fraud is a deliberate error in submitting financial statements. So this study aims to determine the effect of financial stability, financial targets and external pressure on financial statement fraud in energy sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The population in this study were 87 companies, the sampling technique used purposive sampling method and the sample in this study were 16 companies. Secondary data in this study were accessed via www.idx.co.id. To test the research hypothesis, the analysis technique used is quantitative method, including descriptive statistical tests and multiple linear regression tests through SPSS software. The results of this study indicate that simultaneously or partially financial stability, financial targets and external pressure have no effect on fraudulent financial statements.